Immediate Weight Bearing and Range of Motion After Internal Fixation of Unstable Ankle Fractures: A Retrospective Controlled Study. Issue 4 (22nd October 2020) - Fram, Brianna R.; Rogero, Ryan G.; Corr, Daniel; Chang, Gerard; Krieg, James; Raikin, Steven M.
Category: Ankle; Trauma Introduction/Purpose: Ankle fractures are the third most common adult fractures. Further, they are the second most common fracture type to require inpatient admission, behind only hip fractures, despite occurring in a population on average nearly 30 years younger. There is evidence that early or immediate weight bearing and range of motion may be safe following ankle fracture fixation, but existing studies are small and largely exclude patients with syndesmotic or posterior malleolar fixation. We therefore studied the safety of immediate weight bearing as tolerated (IWBAT) and immediate range of motion (IROM) following open reduction internal fixation (ORIF) of unstable ankle fractures in a diverse cohort and attempted to identify risk factors for complications. Methods: We performed a retrospective case-control study. Out of 268 patients who underwent primary ORIF of an unstable ankle fracture from 2013-18, we identified 133 (49.6%) who were IWBAT and IROM. The treating surgeon excluded patients from IWBAT if they had an ipsilateral leg injury requiring non-weight bearing, a large displaced posterior malleolus fragment, or Maisonneuve injury with fracture of the proximal fibula. We used propensity-score matching to identify 172 controls who were non-weight bearing (NWB) and no range of motion for 6 weeks post-op. We reviewed medical records and radiographs for demographic, injury and treatment characteristics. Our primary outcome was complications. We compared demographics, injury characteristics, treatment episode, and complications between the IWBAT and NWB groups and performed within group analysis to identify risk factors for complications. A p-value <0.05 was considered significant. Results: The groups did not differ significantly in age, BMI, Charleston Comorbidity Index (CCI), smoking status, diabetes status, malleoli involved, percentages undergoing medial malleolus (60.9% IWBAT vs. 51.7% NWB, p=0.11), posterior malleolus (24.1% IWBAT, 26.7% NWB, p=0.59), or syndesmosis fixation (41.4% IWBAT, 42.4% NWB, p=0.85). There was no significant difference in total complications (9.8% IWBAT vs. 12.8% NWB, p=0.41), nonoperative complications (6.8% IWBAT vs. 8.7% NWB, p=0.53), or operative complications (3.8% IWBAT vs. 4.1% NWB, p=0.89). We did not identify any factors associated with increased complication risk, including posterior malleolus or syndesmosis fixation, diabetes, age, CCI or pre-injury assisted ambulation. Conclusion: IWBAT and IROM may be safe following ankle fracture ORIF in a broader patient population than previously believed. We did not identify specific risk factors for post-operative complications. Further study on patient selection may allow for more extensive use of this protocol to reduce the morbidity associated with unstable ankle fractures.